Overexpression of TdNACB improves the drought resistance of rice - Fangyi Gong; Tian Zhang; Yusen Lu; Velu, Govindan; Ruiqin Liu; Jia Liu; Xiangquan Wang; Dengcai Liu; Youliang Zheng; Lin Huang; Bihua Wu (Elsevier, 2024)
Drought stress greatly affects disrupts the productivity, ecological structure, physiological and biochemical activities of wheat at different growth stages. However, drought stress tolerance is a complex quantitative trait and involves multiple metabolic pathways. We found that a wild emmer introgression line BAd7-209 had stronger drought resistance compared with drought resistant wheat Zhongmai 175. The transcriptome analysis found 14,284, 22,383 and 21,451 genes had expression corresponding responsed to drought stress at 24h, 48h, 120h, respectively and significantly enriched in ‘Arginine and proline metabolism’ and ‘Peroxisome’ in BAd7-209. 1666 transcription factors (TFs) related responsed to drought stress in which TdNACB showed high expression at 24h, 48h and 120h and had the closest relationship with TaNAC48 and OsNAC6 in phylogenetic analysis. Overexpression of TdNACB significantly enhanced drought resistance in rice and overexpression lines had significantly higher CAT, POD and SOD activity, Pro content and lower MDA content than those of the WT under drought stress. The result demonstrated that TdNACB positively regulates drought resistance through increasing proline content and enhancing activity of enzyme related to ROS scavenging. The results of this study provides candidate genes for improving wheat drought resistance and guide as reference for studying the molecular mechanisms of wheat drought resistance.